Creatures of the Flood - Hunter, Erin (New York, NY : HarperCollins, 2021)
"Three young pandas set out on separate journeys to save their homes and families in the Bamboo Kingdom"--.
Ages 8-12.
Grades 4-6.
Keywords: Pandas -- Fiction; Fantasy